ACUTE AND SUBLETHAL TOXICITY TEST OF PALM OIL WASTES ‎IN THE MAINTENANCE MEDIA OF Clarias gariepinus - Vina Okto Viana; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted on November 9, 2018 until December 15, 2018 at the Laboratory of Environmental Quality of Culture, Faculty of Fisheries and Marine, University of Riau. Objective of this study to determine the effect of palm liquid waste on the acute toxicity test and sub lethal of Clarias gariepinus and safe doses for the growth of C. gariepinus. Determination of 96-h LC50 using the EPA probit method in the SPSS program.Palm liquid waste has an effect on C. gariepinusin the preliminary test the threshold value below 100 ml/L is obtained and the upper threshold value is 1000 ml/L. In acute toxicity the value obtained of 96-h LC50is 417,936 ml / L and ‎the safe biological value (Biological Safety Level) is  4,18 ml/L.‎ In the sublethal test the best treatment during the study was found in treatment P1 (4 ml/L) with absolute weight growth of 4.95 g, specific growth rate of 4.94% and survival of 80%.Keywords: toxicity, acute, sub lethal, palm liquid waste, Clarias gariepinus